The perception of teacher pathways on professional learning - Amaro, Lori Mae Alexandra Marie (Kansas State University, 2021)
This paper explored the similarities and differences between teacher education pathways and perceptions that professional learning had on their teaching practices and teaching self-efficacy. Figuring out how to promote continual learning is critical no matter which pathway a teacher took to get their certification. Many barriers emerged when thinking about and discussing this topic, such as the experiences gained through teacher preparation programs; professional learning formats, content, and quality; district resource allowance; student learning needs; and application of professional learning. All of these elements can influence teachers’ perceptions surrounding professional learning. As educators experience learning opportunities, successful implementation is necessary to see changes in instructional practices, student outcomes, and teacher beliefs and attitudes. The purpose of this study was to explore how elementary ELA teachers in a large Midwestern school district, coming from various pathways into education, perceived professional learning on their classroom practices and teaching self-efficacy. This case study took a qualitative approach by utilizing quantitative data to describe educators’ perceptions. Throughout the study, methods including, surveys, philosophy statements, interviews, classroom observations, field notes, and participant journals, collected data, which assisted in understanding teacher perceptions. Coded and analyzed data formed categories that organized perceptions by professional learning perceptions on teaching practices, professional learning perceptions on teaching self-efficacy, and professional learning perceptions on teaching self-efficacy for those serving students of various populations. Sub-categories broke down the broad categories into definitions/understandings of professional learning and teaching self-efficacy, positive perceptions, and negative perceptions. Other data collected provided connections between perceptions and practices. Participants in this study came from pathways, such as traditional, long-term substitute, accelerated, and other. The results showed that educators need continued support through specialized professional learning, as participants described gaps in their learning that need addressed. Limited professional learning with ReadyGen created a learning gap for teachers. All participants perceived a lack of preparation in working with students of various populations. The conclusion showed that participants, other than the accelerated pathway participant, did not contribute the influence of professional learning to their teaching practices. The conclusion of this study described the need for more specialized learning, especially as new teachers enter the profession, to ensure they are prepared to work in with the diverse students they encounter. In conclusion, recommendations included to continuation of professional learning in smaller settings and an examination of many professional learning aspects within the district.
Keywords: Professional development; Professional learning; Teacher pathways; Teaching self-efficacy